8. SATISFACTION AND RELATIONSHIP OF PATIENTS AT THE DEPARTMENT OF GENERAL EXAMINATION, 108 MILITARY CENTRAL HOSPITAL, 2022 (Vietnam Journal of Community Medicine, 2022)
Objective: To assess patient satisfaction with service quality at the Department of GeneralExamination, 108 Military Central Hospital and finding out some related factors.Subjects and research methods: A cross-sectional descriptive study on 433 patients going to thehospital from April 2022 to July 2022. Tool for data collection was structure questionaire. SolfwareSPSS 26.0 was used to data analysis.Research results: The average overall satisfaction score of patients is 3,54 ± 0,54, belonging to thelevel of satisfaction. Patients were highly satisfied with 4 contents: Medical examination results,staff’s skills and attitudes, medical examination and treatment costs, and landscape environment.Up to 89.9% of patients said they would return for medical examination. In 9 subjects about thecharacteristics of research subjects, the average satisfaction scores differed statistically significantlybetween groups with different levels of education, occupation and distance to the hospital.(p < 0.05).Conclusion: Patients have an overall satisfaction level of service quality at the Department ofExamination is 3.54 ± 0.54, belonging to the level of satisfaction (5-level scale). The remaining fouritems on parking service, waiting time for medical examination, toilet, and waiting area reachedacceptable levels.
Keywords: Hài lòng, chất lượng dịch vụ, khoa Khám bệnh, Bệnh viện Trung ương Quân đội 108.